EVALUATING CONTRAST SENSITIVITY IN AGE-RELATED MACULAR DEGENERATION USING A NOVEL COMPUTER-BASED TEST, THE SPAETH/RICHMAN CONTRAST SENSITIVITY TEST. Issue 7 (July 2015) - Faria, Bruno M.; Duman, Fulya; Zheng, Cindy X.; Waisbourd, Michael; Gupta, Lalita; Ali, Mohsin; Zangalli, Camila; Lu, Lan; Wizov, Sheryl S.; Spaeth, Eric; Richman, Jesse; Spaeth, George L.
<x xml:space="preserve">Abstract</x> Background: Contrast sensitivity (CS) is a valuable measure of visual function in patients with age-related macular degeneration (AMD). The authors aimed to compare a novel computer-based test (the Spaeth/Richman Contrast Sensitivity test) with Pelli–Robson test for evaluating CS in patients with AMD. Methods: In this prospective cross-sectional study, CS was evaluated in patients with various stages of AMD and healthy controls using Spaeth/Richman Contrast Sensitivity test and Pelli–Robson test. Spaeth/Richman Contrast Sensitivity test determined CS scores for 5 areas of vision for each eye (central, superonasal, superotemporal, inferonasal, and inferotemporal) and the total score. Test scores between the two methods were compared using mixed-effects linear regression. Spearman's rank correlation coefficient was used to determine correlations. Test–retest reliability was determined using the intraclass correlation coefficient. Results: Of 35 participants with AMD (54 eyes) and 34 controls (66 eyes), 51% were female and 93% were of European descent. The mean Spaeth/Richman Contrast Sensitivity test score for the central area and each of the 4 peripheral quadrants was significantly lower for patients with AMD versus controls (P < 0.001 for all). The mean Pelli–Robson score was also significantly lower in patients with AMD versus controls (P < 0.001). The intraclass correlation coefficient for Spaeth/Richman Contrast Sensitivity test total score and Pelli–Robson score was 0.87 and 0.92, respectively. Conclusion: Spaeth/Richman Contrast Sensitivity test, a novel Internet-based method of testing CS, had significantly lower scores for patients with AMD compared with controls for central and peripheral vision. This test is a valuable tool for assessing CS in AMD.